Testing and modeling of dowel action for a post-installed anchor subjected to combined shear force and tensile force. (15th September 2019) - Takase, Yuya
Highlights: Post-installed anchors were subjected to shear force and tensile force in the tests. A mechanical model which can estimate the shear load–slip of anchors was proposed. The cyclic behavior of the anchor bolt can be reasonably estimated by the model. Abstract: In seismically active regions, the resistance of buildings against earthquakes must be improved. Post-installed anchors are generally used to connect retrofitting members to existing concrete members of a structure. However, research on the mechanical behavior of post-installed anchors subjected to combined shear and tensile stress is insufficient. Therefore, in this study, loading tests were conducted on anchor bolts by applying cyclic shear loading and constant tensile forces. Additionally, a mechanical model was constructed to evaluate the experimental results. In this model, the shear force was equal to the sum of the bending resistant force at the plastic hinge, the supporting stress of the concrete, and the shear component of the tensile stress of the anchor bolt. The results demonstrate that, with increasing tensile force, the shear force decreases and the joint separation increases. In addition, the proposed model was shown to reasonably replicate the shear load and slip relationship determined from experimentation results.